JUSTIFICATION OF EARLY DIAGNOSTIC AND INTERVENTION ESOPHAGOGASTROSCOPY IN DIAGNOSTICS AND PROPHYLAXIS OF RECURRENCE OF VARICOSE BLEEDINGS - Шестак, Инна Сергеевна; Короткевич, Алексей Григорьевич; Леонтьев, Антон Сергеевич; Кузнецов, Виктор Васильевич; Май, Семен Александрович; Савостьянов, Илья Васильевич (Medicine in Kuzbass, 2018)
Objective. Analysis of medical cards of 257 patients with varicose veins of the esophagus and stomach, who underwent examination and treatment in surgical departments of hospitals in Novokuznetsk in 2011-2017. Men 157 (61 %), women 100 (39 %). The average age of the patients was 52.7 ± 13.5 years.The aim of the study was to determine the structure of bleeding sources with confirmed portal hypertension by using emergency gastroscopy, including to assess the effectiveness of the prevention of hemorrhagic recurrence using endoscopic hemostasis methods.Methods. Gastroscopy was performed in 165 (64.2 %) patients on average 2.2 ± 0.5 hours from the admission by endoscopes Olympus, Karl Storz and Fujinon with an instrumental channel of 2.8 mm. The presence of varicose veins of the esophagus and stomach, the degree of their expansion, the extent, activity of bleeding, the presence of other sources were evaluated.Results. Sources of bleeding in patients with confirmed portal hypertension were non-varicose causes in 34 %. In the structure of bleeding complicating portal hypertension, the share of non-varicose bleeding was only 17.5 %. The effectiveness of endoscopic hemostasis in comparison with the Blackmore probe showed the obvious advantages of endoscopy (χ2 = 9,865; р = 0,0001). Mortality with the use of emergency endohemostasis was significantly lower in comparison with the traditional application of the Blackmore probe (χ2 = 3.712; p = 0.044). The frequency of recurrence of hemorrhage was also significantly lower with endoscopy (χ2 = 20.22; p = 0.0000).Conclusions. Portal hypertension in 34 % accompanies non-varicose sources with localization from the esophagus to duodenum. Emergency interventional endoscopy on admission allows patients to monitor hemostasis reliably, to reduce the frequency of relapses and mortality.
Keywords: esophageal varices bleeding; emergency esophagogastroscopy; endoscopic hemostasis